2011
DOI: 10.1029/2010tc002808
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Pliocene exhumation of the central Greater Caucasus constrained by low‐temperature thermochronometry

Abstract: [1] Constraining the timing of onset and rates of deformation within the Greater Caucasus mountains is key to understanding their role in accommodating deformation across the Arabia-Eurasia orogen. We present new low-temperature thermochronometric constraints on the Cenozoic thermal evolution of the central Greater Caucasus that elucidate a three-phase cooling history. Between 50 and 30 Ma, cooling within the range was negligible. In Oligocene time, cooling rates throughout the range increased to ∼4°C/Myr. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
180
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(198 citation statements)
references
References 100 publications
(190 reference statements)
17
180
1
Order By: Relevance
“…Lozar & Polino 1997;Adamia et al 2011) draw similar conclusions, and abundant evidence exists that Crimea experienced Eocene, then Oligocene, uplift (Panek et al 2009;Nikishin et al 2017). Conversely, Avdeev & Niemi (2011), Forte et al (2014 and Cowgill et al (2016) have suggested that the major phase of uplift occurred no earlier than c. 5 myr ago, whereas Rolland (2017) prefers a Miocene (c. 15 Ma) age for the onset of Caucasus uplift, based on geodynamic context and fission-track constraints on 'hard' Arabia-Eurasia collision (e.g. Okay et al 2010).…”
Section: Et Al 2000)supporting
confidence: 50%
“…Lozar & Polino 1997;Adamia et al 2011) draw similar conclusions, and abundant evidence exists that Crimea experienced Eocene, then Oligocene, uplift (Panek et al 2009;Nikishin et al 2017). Conversely, Avdeev & Niemi (2011), Forte et al (2014 and Cowgill et al (2016) have suggested that the major phase of uplift occurred no earlier than c. 5 myr ago, whereas Rolland (2017) prefers a Miocene (c. 15 Ma) age for the onset of Caucasus uplift, based on geodynamic context and fission-track constraints on 'hard' Arabia-Eurasia collision (e.g. Okay et al 2010).…”
Section: Et Al 2000)supporting
confidence: 50%
“…2a), mean k sn and S avg (Fig. 6c) with apatite (U-Th)/He and fission track cooling ages (Avdeev, 2011;Avdeev and Niemi, 2011;Král and Gurbanov, 1996;Vincent et al, 2011) suggest broadly similar patterns (Figs. 2 and 3).…”
Section: Connecting Topography Implied Erosion Rates and Thermochromentioning
confidence: 55%
“…1, Mosar et al, 2010) and are underlain by a north dipping subducted slab extending to at least 160 km depth (Mumladze et al, 2015). Thermochronometric data suggest more rapid uplift of ∼1 mm/y in the center of the range, with slower rates of exhumation as low as 0.1 mm/y along the tips (Avdeev, 2011;Avdeev and Niemi, 2011;Král and Gurbanov, 1996;Vincent et al, 2011). However, data is concentrated in the western GC so it is unclear if this pattern continues eastward (Fig.…”
Section: Tectonic Settingmentioning
confidence: 84%
See 1 more Smart Citation
“…The high geothermal gradients associated with the volcanism therefore imply that earthquakes are only likely to occur down to depths of less than 10-15 km, as observed in most other mountain ranges [Molnar and Lyon-Caen, 1989;Nissen et al, 2011]. One possibility for the deep extent of slip in the 2011 Van event lies within the portion of the Arabian Plate that was underthrust beneath the southern margin of the Turkish-Iranian Plateau before shortening jumped north to the Greater Caucasus at 5 Ma [Avdeev and Niemi, 2011]. Lake Van lies at the northern edge of the region of efficient Sn propagation mapped by Gök et al [2003], who suggest that the lithospheric mantle is hot or absent north of this boundary, and cooler south of it.…”
Section: Tectonics Of the Turkish-iranian Plateaumentioning
confidence: 99%